Symptoms and Signs Associated with Postpartum Thyroiditis. (27th October 2014) - Groer, Maureen; Jevitt, Cecilia
Abstract : Background. Postpartum thyroiditis (PPT) is a common triphasic autoimmune disease in women with thyroid peroxidase (TPO) autoantibodies. This study evaluated women's thyroid disease symptoms, physical findings, stress levels, and thyroid stimulating hormone (TSH) levels across six postpartum months in three groups, TPO negative, TPO positive, and PPT positive women. Methods. Women were recruited in midpregnancy ( n = 631 ) and TPO status was determined which then was used to form the three postpartum groups. The three groups were compared on TSH levels, thyroid symptoms, weight, blood pressure, heart rate, a thyroid exam, and stress scores. Results. Fifty-six percent of the TPO positive women developed PPT. Hypothyroid group ( F (2, 742) = 5.8, P = . 003 ) and hyperthyroid group ( F (2, 747) = 6.6, P = . 001 ) subscale scores differed by group. Several symptoms and stress scores were highest in the PPT group. Conclusions. The normal postpartum is associated with many symptoms that mimic thyroid disease symptoms, but severity is greater in women with either TPO or PPT positivity. While the most severe symptoms were generally seen in PPT positive women, even TPO positive women seem to have higher risk for these signs and symptoms.